2020
DOI: 10.1111/ijcp.13733
|View full text |Cite
|
Sign up to set email alerts
|

Management of intermediate‐stage hepatocellular carcinoma in the elderly with transcatheter arterial chemoembolization failure: Retreatment or switching to systemic therapy?

Abstract: Background Transcatheter Arterial chemoembolization (TACE) is the first‐line option for the intermediate‐stage hepatocellular carcinoma. Guidelines do not define the number of TACE sessions to be repeated before stopping treatment and switching to sorafenib. Methods We retrospectively analysed 76 patients aged ≥65 years who were treated by multiple TACE sessions (re‐TACE group; N = 36 patients) or one TACE session followed by sorafenib (TACE/Sorafenib group; N = 40 patients). The primary outcome was the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…18,19 Sorafenib, a representative oral tyrosine kinase inhibitor (TKI) agent that can target vascular endothelial growth factor (VEGF) to normalize tumor vasculature, has displayed inspiring tumor control and prognosis for subsequent treatment after TACE refractoriness. 13,20 Shimose et al found that TACE-refractory patients treated with lenvatinib reached a significantly longer median PFS than those treated with sorafenib and TACE (5.8 vs 3.2 vs 2.4 months). 21 Compared with sorafenib, lenvatinib is another oral TKI that involves more potent inhibition of VEGFR and a distinct mechanism of action with unique inhibition of fibroblast growth factor receptor in patients with advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Sorafenib, a representative oral tyrosine kinase inhibitor (TKI) agent that can target vascular endothelial growth factor (VEGF) to normalize tumor vasculature, has displayed inspiring tumor control and prognosis for subsequent treatment after TACE refractoriness. 13,20 Shimose et al found that TACE-refractory patients treated with lenvatinib reached a significantly longer median PFS than those treated with sorafenib and TACE (5.8 vs 3.2 vs 2.4 months). 21 Compared with sorafenib, lenvatinib is another oral TKI that involves more potent inhibition of VEGFR and a distinct mechanism of action with unique inhibition of fibroblast growth factor receptor in patients with advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…TACE refractoriness/failure is speculated to be related to tumor neovascularization after consecutive superselective TACE procedures 18,19 . Sorafenib, a representative oral tyrosine kinase inhibitor (TKI) agent that can target vascular endothelial growth factor (VEGF) to normalize tumor vasculature, has displayed inspiring tumor control and prognosis for subsequent treatment after TACE refractoriness 13,20 . Shimose et al .…”
Section: Discussionmentioning
confidence: 99%
“…The long treatment time after tumor progression may have challenged the efficacy of sorafenib. Recently, Villani et al25 reported results that conflicted with those of the two aforementioned studies. Their study included 76 elderly patients ≥65 years of age with intermediate-stage HCC after TACE failure/refractoriness.…”
mentioning
confidence: 90%